Hand Index and Psychiatric Illness - Atal, D K; Bhatt, N; Sulaiman, M S; Das , S (Journal of Indian Academy of Forensic Medicine, 2015)
The shape of the hand has been considered as an important criterion in the study of palmistry and other related sciences since ancient times. A scientific measurement of the shape of the hand can be achieved by calculating its breadth and length, taking into consideration its various landmarks. Previous workers have studied the various measurements related to the human hand and have pointed out significant association with various diseases. However, such studies are few in number. Hand index is found to be an important tool in determination of nature, personality, predisposition to certain diseases, and many other unique points about an individual. The current study was conducted in the Outpatient Department of Psychiatry of the Himalayan Institute Hospital, Dehradun. The hand index of patients with psychiatric illness was studied and the results were compared with a control group. An effort was made to find out whether there is any correlation between dimensions of the hand and presence of psychiatric morbidity of an individual.